Leadership behaviors in project management at software industries in Klang Valley / Maizan Saad (Hj) - Saad, Maizan (Faculty of Information Technology and Quantitative Sciences, 2005)
There are many factors that lead to the unsuccessful or failure of Information Technology (IT) projects and one of the factors is lack of leadership among IT managers. According to Copeland (2004), he defined that project failure as 'Hhe high level of project failures directly attributed to the lack of leadership capabilities of the project manager". Therefore, the purpose of this research is to identify the most important leadership qualities and behaviors needed as well as the leadership roles effectiveness in project management for effective leadership. The methodologies used are questionnaires and interview. There are 121 respondents from three organizational roles which are project managers themselves, their superiors and subordinates that have been completed and returned the questionnaires. Whereas, seven project managers have been interviewed. According to the project managers, all the 12 leadership qualities tested are needed for effective leadership. While, all the 11 of leadership behaviors tested based on Yukl's Taxonomy are needed for effective leadership and the three most important behaviors identified by the project managers were planning and organizing (M=31.7%), problem solving (M=22.2%) and Consulting and Delegating (M=19%). Whereas, the least important behaviors were Recognizing and Rewarding (L=28.6%), Monitoring (L=22.2%) and Motivating and Inspiring (L=15.9%). In term of leadership roles effectiveness, based on the project managers' perspectives, they agree the leadership roles effectiveness is depend on managerial experience and education level, whereas their subordinates agree the leadership roles effectiveness is depend on age, gender and education level and their superiors agree the leadership roles effectiveness is depend on managerial experience. So, the researcher found that the education level and managerial experience are the most perceived to lead for effective leadership roles. In conclusion, the researcher hope that if the importance of leadership qualities, behaviors and the effectiveness of leadership roles can be gathered and accomplished together by the project managers, it would lead for effective leadership as well as for the successful of project leaders in project management.